Reducing Poverty, Protecting Livelihoods, and Building Assets in a Changing Climate : Social Implications of Climate Change for Latin America and the Caribbean - Verner, Dorte (World Bank, 2012)
This book provides a much needed look at the impact of climate change on the poor. It convincingly demonstrates that issues of poverty and livelihoods must be integrated into climate change policies to help achieve sustainable development gains. The high incidence of natural disasters, growing urbanization, and increased water scarcity combined with the acute impact of these phenomena on the poor and vulnerable complicates the already enormous challenge of reducing poverty and inequality in Latin America and the Caribbean. This publication lays bare the social implications of climate change and equips the reader with a framework for understanding how climate change and climate variability affect livelihoods, poverty, income, health, and migration. These scenarios call for greater efforts to incorporate poverty, livelihood, and social considerations into climate change adaptation and mitigation policies. Purposefully targeted policies and investments can support economic growth and poverty reduction efforts and help achieve sustainable development goals. In other words, good climate change adaptation policies can also be good development policies. This book will change the way the author think about the relationship between poverty, social development, and climate change. It provides climate-smart policy options to help reduce vulnerability, protect livelihoods, and build communities that are resilient to changing climate conditions.